2012
DOI: 10.1002/chem.201103920
|View full text |Cite
|
Sign up to set email alerts
|

Directed Remote Aromatic Metalations: Mechanisms and Driving Forces

Abstract: Directed remote aromatic metalations are useful synthetic transformations allowing for rapid regioselective access to elaborate highly substituted carbocyclic aromatic and heteroaromatic systems. This review unravels the tangle of data reported on directed remote aromatic metalations. Through a careful analysis of critically selected examples, advanced rationalizations of remote metalation regioselectivities are presented. These extend beyond the complex-induced proximity effect (CIPE). Mechanisms, driving for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 129 publications
0
33
0
Order By: Relevance
“…The K + ([18]crown-6) part can interact with the fluorine on the silicon atom in 4 to place the center anion F À near the boron atom, [22] which facilitates the nucleophilic attack of F À on the boron by a kind of complex-induced proximity effect. [23] We performed DFT calculation of 7 (cis form) and its trans isomer including the K + /[18]crown-6 part (see the Supporting Information). [24] The calculation showed that 7 was more stable than the trans isomer by 5.44 kcal mol À1 .…”
mentioning
confidence: 99%
“…The K + ([18]crown-6) part can interact with the fluorine on the silicon atom in 4 to place the center anion F À near the boron atom, [22] which facilitates the nucleophilic attack of F À on the boron by a kind of complex-induced proximity effect. [23] We performed DFT calculation of 7 (cis form) and its trans isomer including the K + /[18]crown-6 part (see the Supporting Information). [24] The calculation showed that 7 was more stable than the trans isomer by 5.44 kcal mol À1 .…”
mentioning
confidence: 99%
“…It is known for decades [ 33 ] that cooperative effects of directing groups lead to directed ortho -metalation (DoM) at their common ortho -position (C-6 in this case, located ortho to both the amide and the methoxy group). Nevertheless, under reversible metalation conditions, typically existing when amide bases like LDA are employed, kinetically controlled DoM can be followed by an equilibration to give a thermodynamically controlled DreM product [ 34 ]. This has been demonstrated by Tilly et al [ 35 ] in the synthesis of fluorenones by treatment of N , N -dialkyl biphenyl-2-carboxamides with LDA.…”
Section: Resultsmentioning
confidence: 99%
“…The observed ortho-directing ability of the azetidine ring could be explained by assuming the coordinating role of the nitrogen atom, as seen in the case of 2-arylaziridines or other Lewis basic heteroatoms that bear an aromatic ring. [28,[3][4][5] However, as in the case of N-alkyl-2-arylaziridines (Scheme 1), the importance of dynamic phenomena on the reactivity should be taken into consideration. We envisaged that N-alkyl-2-arylazetidines could also show dynamic phenomena associated with both nitrogen inversion (NI) and additional ring puckering (RP).…”
Section: Resultsmentioning
confidence: 99%